Dynamics of 137Cs specific activity in Convalaria Majalis L. in Polissia forests of Ukraine after the accident at Chornobyl Nuclear Power Plant - V. P. Krasnov; V. V. Melnik; T. V. Kurbet; O. V. Zhukovsky; O. V. Zborovska; O. O. Orlov (Ядерна фізика та енергетика)
Results of many years of the research on 137Cs accumulation of Lily of the valley (Convallaria majalis L.) in the above-ground phytomass in wet sugrudy of the mixed forests of Zhytomyr Polissia are presented. The radionuclide specific activity in Lily of the valley decreased by 11.1 - 17.3 times during the observation period (1991 - 2018). The increase of this indicator was revealed in certain years and periods, which is possibly due to weather conditions of particular year and cyclic migration of 137Cs in forest biogeocoenosis. The dependence between the density of 137Cs radioactive contamination of soil and the content of radionuclide in grass as well as in common inflorescences of Lily of the valley is revealed.